Negosiasi Sebagai Forum Aps: Kajian Teoritis dan Praktis di Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Negotiation is the most fundamental form of Alternative Dispute Resolution (ADR), emphasizing the peaceful settlement of conflicts through direct dialogue between disputing parties without involving a third party. In Indonesia, negotiation has become one of the most widely used ADR mechanisms and has developed across various fields, including civil law, labor relations, administrative disputes, and environmental issues. This study aims to analyze negotiation as an ADR forum from two main perspectives. First, a theoretical review that examines the principles of negotiation, its stages, as well as its advantages and limitations compared to other dispute resolution mechanisms. Second, a practical review that elaborates on the implementation of negotiation within the Indonesian legal context through case studies of disputes resolved through negotiation. The research employs a normative-juridical approach to analyze the legal foundations and principles governing negotiation, combined with an empirical review through case data exploration and interviews with legal practitioners. The findings indicate that negotiation offers several advantages, including efficiency in time and cost, procedural flexibility, and the potential for mutually beneficial solutions (win–win solutions). However, this study also identifies challenges such as unequal bargaining positions between parties, limited legal recognition of negotiation outcomes, and the insufficient capacity of negotiators or informal mediators to fully grasp legal aspects. Based on these findings, the study recommends several strategic steps: enhancing legal recognition and protection for negotiation outcomes, strengthening the capacity and competence of negotiators through legal and communication skills training, and expanding the use of negotiation as an initial step in resolving various types of disputes. With stronger legal frameworks and improved human resources, negotiation has the potential to become a more effective, efficient, and sustainable dispute resolution instrument in Indonesia.